Pembuatan Tanaman Obat Keluarga (TOGA) di RW 5 Kelurahan Pebatuan Pekanbaru dalam Program Kerja Praktek Kerja Nyata Mahasiswa Poltekkes Kemenkes Riau - Delvira, Wiwiek; Uthia, Rahimatul; Rz, Ira Oktaviani; Jannah, Fathul; Idayanti, Idayanti (Poltekkes Kemenkes Riau, 2025)
The planting of Family Medicinal Plants (TOGA) in RW 5 Pebatuan Subdistrict Pekanbaru was conducted as part of the Community Service program of Poltekkes Kemenkes Riau students on May 9, 2025. This activity is a collaboration among lecturers, students, and local residents in empowering the community to provide and manage the TOGA garden. The method involved active community participation under the guidance of students and lecturers, resulting in the establishment of a medicinal plant garden that can be used for family health needs and community education. The results showed the success of the TOGA garden establishment with various medicinal plants beneficial for health and economic potential. This program is expected to be a model for community empowerment and the development of medicinal plants based on local wisdom.